Using the Isolated Rat Placenta to Assess Fetoplacental Hemodynamics - Garner, K. L.; Bowdridge, E. C.; DeVallance, E.; Griffith, J. A.; Kelley, E. E.; Nurkiewicz, T. R. (Frontiers in Toxicology, 2022)
Placental health is critical to fetal growth and maternal health during gestation. However, investigating placental flow in an ex-vivo isolated system where inflow is independently controlled has yet to be developed in the rat. Here, we describe a novel technique, isolated perfused placenta technique that allows for analysis of placental pressure outflow pressure, placental flow in rats at gestational day 20. Using this method, we successfully perfused placentas from dams and were able to observe increases in outflow pressure and flow as the inflow pressure to the placenta was increased in a step wise fashion. This method will help to advance the functional analysis of placental flow and therefore placental resistance and efficiency.